A linear static analysis of truss footbridge - Nur Shafiqa, Suhaimi (2013)
The purpose of this dissertation is to study a linear static analysis of truss footbridge in different shape of truss. The important of this study come out where sometimes an engineer is taking much time or difficult to choose an effectives truss shape to design in real structure. In analysis, three shapes of truss are choosing which are Warren, Pratt, and Howe truss with pinned and roller support at the end of the bridge. The design loads which are pedestrian loads are distributed to the joints on bridge deck. A total of three shapes truss with 6 modelled were investigate and analyse using ANSYS+Civi1FEM software. The analysis of all sets of trusses is dividing with two groups. The first group is all load is applied along the bridge deck for three shapes of truss footbridge. For the second group, the load is applied at the mid span of bridge deck. The analysis of all sets of trusses use the same length of the span, same loads and same height of the truss footbridge. The effective of truss shape is determined when the truss footbridge has the lowest displacement and lowest axial stress. The most effectives truss footbridge is depend on number of members and arrangement of member. All the member of the truss footbridge has compression or tension force. The truss footbridge analysis is successfully modelled using ANSYS+CivilFEM software and finite element method.